Psychopathology and Quality of Life in Traumatized or Victimized Underage Individuals as Factors for Forensic Multilevel Assessment—A Pilot Investigation - Voelkl-Kernstock, Sabine; Kletecka-Pulker, Maria; Felnhofer, Anna; Kothgassner, Oswald David; Skala, Katrin; Hansmann, Brigitte; Wenzel, Thomas (Frontiers in Psychiatry, 2019)
Background: Psychological sequels to criminal violence can be long lasting and severe. They are in many countries not sufficiently considered in court cases as an important circumstance that could be used to assess the severity of the crime, also guiding redress, compensation, and rehabilitation of the victim, and—in children—child custody considerations. So far, the focus of forensic assessment has often been limited to diagnostic categories, especially “posttraumatic stress disorder” (PTSD), a diagnosis that presently is subjected to rapidly changing definitions both in and between diagnostic systems. Other indicators such as quality of life (QoL) might be of equal importance as compared to clinical or research diagnostic categories to understand and evaluate the impact of a crime and the amount of help needed and, in the legal context, redress to be asked. Symptoms might differ depending on the crime encountered. Objective and Methods: QoL and general symptom patterns including a PTSD diagnosis were assessed in a group of 10- to 17-year-old minors with (n = 33) and without (n = 49) PTSD diagnosis who all had experienced sexual abuse, physical abuse, death of a parent, or their parents’ divorce, using standardized diagnostic instruments. Results: PTSD patients reported a significantly lower QoL than non-PTSD controls. Reported symptom patterns with potential impact on life, such as intrusive thoughts, differed between the victims of different crime types, with the highest rates of both intrusive symptoms and combined symptom profile in victims of sexual abuse. Data indicate that the changes between older and present criteria and between DSM and recently published ICD 11 might help identify different groups and symptom profiles. Conclusion: Specific trauma-related symptom profiles integrating the type of crime encountered and its individual impact on QoL may help improve future forensic assessment and guide compensation and rehabilitation plans. Carefully designed studies are now needed to further explore the use and forensic usability of complex indicators and the impact of violence in different forensic settings.